Design of a fluidic chamber for the analysis of diffusion CPA/VA in a single cell using Raman microscopy - Hubenia, Oleksandra; Tewes, Rouven; Leal-Marin, Sara; Winkler, Christina; Iddi, Abdul-Rashid; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):237